2016
DOI: 10.3390/app6060170
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Extraction of Cellulose and Synthesizing Pharmaceutical Grade Carboxymethyl Sago Cellulose from Malaysian Sago Pulp

Abstract: Abstract:Sago biomass is an agro-industrial waste produced in large quantities, mainly in the Asia-Pacific region and in particular South-East Asia. This work focuses on using sago biomass to obtain cellulose as the raw material, through chemical processing using acid hydrolysis, alkaline extraction, chlorination and bleaching, finally converting the material to pharmaceutical grade carboxymethyl sago cellulose (CMSC) by carboxymethylation. The cellulose was evaluated using Thermogravimetric Analysis (TGA), In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 61 publications
2
18
0
1
Order By: Relevance
“…Adding carboxymethyl cellulose improved starch network so that starch could form hydrogenous bond with hydroxyl and carboxyl groups of carboxymethyl cellulose macromolecules, leading to reinforcement of structure and reduction in diffusion of water molecules through starch network. Similar results were also obtained by other researchers who observed reduction of water absorption by polymeric mixtures and bio-composites via adding cellulose-hemicellulose fibers [1,5,13,16]. Increased concentration of carboxymethyl cellulose reduced humidity absorption of composite films.…”
Section: Absorption Isothermsupporting
confidence: 79%
See 4 more Smart Citations
“…Adding carboxymethyl cellulose improved starch network so that starch could form hydrogenous bond with hydroxyl and carboxyl groups of carboxymethyl cellulose macromolecules, leading to reinforcement of structure and reduction in diffusion of water molecules through starch network. Similar results were also obtained by other researchers who observed reduction of water absorption by polymeric mixtures and bio-composites via adding cellulose-hemicellulose fibers [1,5,13,16]. Increased concentration of carboxymethyl cellulose reduced humidity absorption of composite films.…”
Section: Absorption Isothermsupporting
confidence: 79%
“…Other researchers investigated effect of calcium chloride on physical and mechanical properties of alginate-sago edible films. Increased concentration of calcium chloride increased tensile strength of alginate-sago edible films but increased elongation percent of these films [1,5,10,13].In some cases, reported that adding carboxymethyl cellulose to soy protein film could improve mechanical properties of these films due to reaction and connection between polymeric chains of protein [14,15]. Parra et al conducted studies on mechanical properties of edible films caused by cassava starch.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations